PERAN GURU MENGASAH POLA PIKIR KRITIS MELALUI METODE DISKUSI DAN TANYA JAWAB SISWA KELAS 3A DI SDN 08 MAMBORO - Wahyu Cahyani; Redna (EDU RESEARCH, 2024)
This study aims to explain the importance of the teacher's role in developing students' critical thinking skills through the discussion and question-and-answer method. The main subjects of this study were 19 third-grade students of class IIIA at SDN 08 Mamboro. This Classroom Action Research adopted the John Elliott model, where each cycle consisted of four main activities: planning, implementation, observation, and reflection, conducted over two cycles. Data collection techniques involved observation and interviews, while data analysis was carried out using a descriptive qualitative-quantitative approach. Quantitative analysis was used to determine the improvement in results through percentages. The findings showed that in the first cycle, student participation was still low (31.58%) due to a lack of understanding of the material and low self-confidence. A significant improvement in the second cycle (73.68%) demonstrated that guided discussions and structured question-and-answer sessions are effective in enhancing critical thinking skills. This proves that fostering critical thinking skills in students can prepare them to face higher-order thinking challenges and is relevant for implementation across various learning contexts.